ANALYSIS OF MUD VULCANO (LUSI) EMBANKMENT DAMS STABILITY WITH SHEET PILE AND PVD USING FINITE ELEMENT METHOD (FEM) - Ach Bustomi Zuhri; Moch. Sholeh; Mohamad Zenurianto (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
The Lumpur Sidoarjo air shelter at point 68 in the Kedungbendo area had a loosening on April 10, 2018. It is frequently employed to analyse the use of finite elements in an effort to find the slope's security factor. Through software modelling, the researchers attempted to evaluate the parameters that affected the lapindo mud slopes' stability. The Mohr-Coulomb method and 2D Plaxis V20 are used in conjunction with the finite element method. Furthermore, a comparison is performed using the Geo5 2024 Trial Version application. We can ascertain the influence of the seismic-free slope security factor and its impact according to SNI using this geotechnical assistance programme. The Geotechnical Aid Program's security factor values are nearly same, and the Geo5 2024 Trial. The difference is caused by the addition of the modulus unloading and reloading parameter in version. Additionally, the study assessed the efficiency of prefabricated vertical drains (PVD) and sheet piles for slope reinforcement. In the absence of PVD, the 90% consolidation time equals 868.3 days, so the safety factor is 1.59. With PVD, the 90% integration time is only 258 days, and the safety factor is 1.60. PVD has been shown to be an effective instrument for accelerating the soil consolidation process without compromising the structure's stability.